1H time domain NMR real time monitoring of polyacrylamide hydrogels synthesis. (July 2017) - Rodrigues, Elton J.R.; Sebastião, Pedro J.O.; Tavares, Maria I.B.
Abstract: Synthesis reactions of polyacrylamide based hydrogels were automatically monitored in situ by time-domain nuclear magnetic resonance, through a steady-state pulse sequence. Four hydrogel formulations with different amounts of monomer and crosslinking agent were tested and the proposed method demonstrated sensitivity to each formulation without the need for a priori calibration of the spectrometer, even when the hydrogels exhibited substantially different structural characteristics. The results obtained by the proposed method were compared for validation with those generated by traditional reaction monitoring methods, such as UV–Vis spectroscopy, and exhibited similar results, suggesting that time-domain nuclear magnetic constitutes an interesting alternative for the monitoring of solution crosslinking reactions.